Applications of artificial intelligence and urban innovation performance: A quasi-natural experiment based on the pilot zones for the innovative application of artificial intelligence - Shuang Han; Xianmin Sun; Shen Zhong (PLoS ONE, 2025)
Innovation is the core driving force behind the ability to cope with risks and enhance urban competitiveness. Against the backdrop of frequent global crises and intensified competition, improving urban innovation performance is important. This study uses 283 Chinese cities from 2012 to 2023 to empirically analyze the impact of artificial intelligence (AI) applications on urban innovation performance and the underlying mechanism. The results show that AI significantly promotes urban innovation performance while simultaneously improving both the quality and quantity of urban innovation. Moreover, through testing, it was found that the enhancement of human capital and absorptive capacity has become an important channel through which AI drives urban innovation. Additionally, the degree of government intervention weakens the positive impact of AI applications on urban innovation performance. Further research reveals that the impact of AI applications on urban innovation performance varies according to geographical region, implementation time of policies, and scale of cities.